Moderating Effect of Trust in Managers on the Relation between Delegation of Authority and Managers’ Perceived Social Loafing - Bozkurt, F. Gamze (Information Management and Business Review, 2012)
Delegation of authority is the manager’s transferral of his/her right of decision-making and implementation to subordinates. Delegation is widely acknowledged an essential element of effective management. Although delegation of authority is used as a managerial technique, employees might perceive it as either social loafing behaviour by their manager or an empowerment method. One of the purposes of the current study is to determine whether delegation of authority is perceived as a kind of social loafing behaviour or not. According to some researchers, trust affects how one interprets managers’ behaviours and the motives underlying them. If employees trust their managers, they become more positive about their managers and may even ignore some of their behaviours. Therefore, the second purpose of the current study is to investigate the moderating effect of trust on the relationship between the delegation of authority and subordinates’ perceptions of their managers’ social loafing. Data were collected from 243 employees working in a company. Hierarchical regression analysis was used to in order to measure linear and moderator effects. The results revealed that there is no relationship between the delegation of authority and perceived social loafing. Moreover, it was found that the level of trust in managers does not moderate this relationship. Interestingly, although it was not hypothesized, further analysis revealed that trust in manager is negatively related to the manager’s perceived social loafing. The implications of the study for research and practice are discussed and some suggestions are made for future research as well as the strengths and limitations of the study.